Identification of Student Misconceptions on Photoelectric Effect Materials Using Four-Tier Diagnostic Test - Pasaribu, Yessi Hani; Sari, Lindya; Sinaga, Wendah Afniati (Golden Ratio of Data in Summary, 2025)
This study aims to identify the level of misconceptions that occur in students by applying the four-tier diagnostic test method on photoelectric effect material. This research uses descriptive research with a quantitative approach. The samples of this research were 25 students of semester VII D and IX of physics education study program of Medan State University. The research instrument in the form of a four-tier diagnostic test using google form which consists of four levels, namely questions with one correct answer along with three exceptions, the level of confidence in the answer, the reason, and the level of confidence in the reason. The data collection technique used is by filling out the diagnostic test using. The data analysis technique used in this research is descriptive quantitative by finding the percentage of student misconceptions in each question. From the results of the study, it can be seen that students experience misconceptions in each question of photoelectric effect material with an average percentage of misconceptions of 34.67%. This percentage is classified as moderate category misconceptions. The highest percentage of misconceptions occurred in questions number 1 and 2 by 40%. The implication of this research is that educators can analyze the misconceptions experienced by students, and use suitable learning methods so that these misconceptions do not recur.